Perbandingan Metode Monte Carlo Antithetic Variate dan Control Variate dalam Penentuan Harga Opsi Barrier Knock-Out - Murwaningtyas, Chatarina Enny; Haryono, William Saputra; Uge, Maria Andriani; Kristofel, Tedi (Universitas Negeri Gorontalo, 2024)
This study aims to examine the effectiveness of the Monte Carlo antithetic variate and control variate methods in pricing knock-out barrier options compared to the standard Monte Carlo method. The main problem in barrier option pricing is the high variance of estimates, which can reduce the accuracy and efficiency of results. The standard Monte Carlo method often requires a very large number of simulations to achieve stable results, which is computationally inefficient. To address this issue, this study employs variance reduction techniques, antithetic variate, and control variate. The findings indicate that both methods offer higher accuracy in price estimation compared to the standard Monte Carlo method. Further analysis reveals that the control variate method is more effective for pricing up and out barrier call options and down and out barrier call options, while the antithetic variate method excels in pricing up and out barrier put options and down and out barrier put options. This study underscores the importance of selecting the appropriate method according to the type of option involved to achieve accurate and efficient estimations.